2005
DOI: 10.17221/3606-pse
|View full text |Cite
|
Sign up to set email alerts
|

<sup>15</sup>N natural abundances in two podsol soils of two spruce forests differing in their atmospheric N deposition conditions

Abstract: This study aims to investigate the changes in isotope ratios in foliage and soils of the two spruce forests [Picea abies (L.) Karst.] differing greatly in their atmospheric N deposition and climatic conditions. As expected, both N concentrations and δ 15 N values in both needles and li�er were found to be significantly higher in the Solling stand (N-saturated) compared to the Hyytialä stand (N-poor). For the N-limited site (Hyytialä plot), a typical vertical gradient of the soil 15 N-enrichment (both in organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In contrast, the higher  15 N values measured in terrestrial herbivore bone collagen appear to reflect the  15 N values of some modern terrestrial plants in proximity to the lake, which are in the range 1.3‰ to 2.6‰. Investigation of plant  15 N around Mývatn did not suggest enrichment due to midge infall into terrestrial habitats (Gratton et al 2008); however, plant  15 N may be increased as a result of artificial fertiliza- Meints et al 1975;Sah 2005). Fertilization may also have formed a significant part of Norse agricultural practices in Mývatnssveit (McGovern et al 2007;Adderley et al 2008).…”
Section: Discussionmentioning
confidence: 83%
“…In contrast, the higher  15 N values measured in terrestrial herbivore bone collagen appear to reflect the  15 N values of some modern terrestrial plants in proximity to the lake, which are in the range 1.3‰ to 2.6‰. Investigation of plant  15 N around Mývatn did not suggest enrichment due to midge infall into terrestrial habitats (Gratton et al 2008); however, plant  15 N may be increased as a result of artificial fertiliza- Meints et al 1975;Sah 2005). Fertilization may also have formed a significant part of Norse agricultural practices in Mývatnssveit (McGovern et al 2007;Adderley et al 2008).…”
Section: Discussionmentioning
confidence: 83%
“…Mean δ 15 N values of FF samples indicate that the mid-age plots were depleted in the heavier isotope relative to their younger plot pairs (Table 3). Two plausible explanations for the trend shown in our data are (i) the mid-age plots were covered with significant feather moss and lichens that have been reported to have more depleted 15 N as a result of N 2 fixation (DeLuca et al, 2002;Lavoie et al, 2007); and (ii) fresh litter inputs, which is generally depleted in the heavier isotope than old litter (Sah, 2005), exceed output for the mid-age forest stands than the young stands (Diochon and Kellman, 2008). Pardo et al (2002) reported a 1‰ increase in δ 15 N 3 years after clear cutting as a result of nitrification and nitrate loss in New Hampshire.…”
Section: Bulk Density and C And N Concentration And Massmentioning
confidence: 60%